Enablers and barriers to vaccine uptake and handwashing practices to prevent and control COVID-19 in Kenya, Uganda, and Tanzania: a systematic review - Muchangi, Josphat Martin; Mturi, James; Mukasa, Hajra; Kithuki, Kioko; Kosgei, Sarah Jebet; Kanyangi, Lennah Muhoja; Moraro, Rogers; Nankanja, Maureen (Frontiers in Public Health, 2024)
The global emergence of coronavirus disease 2019 (COVID-19) posed unprecedented challenges, jeopardizing decades of progress in healthcare systems, education, and poverty eradication. While proven interventions such as handwashing and mass vaccination offer effective means of curbing COVID-19 spread, their uptake remains low, potentially undermining future pandemic control efforts. This systematic review synthesized available evidence of the factors influencing vaccine uptake and handwashing practices in Kenya, Uganda, and Tanzania in the context of COVID-19 prevention and control. We conducted an extensive literature search across PubMed, Science Direct, and Google Scholar databases following Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Out of 391 reviewed articles, 18 were eligible for inclusion. Some of the common barriers to handwashing in Kenya, Uganda, and Tanzania included lack of trust in the government’s recommendations or messaging on the benefits of hand hygiene and lack of access to water, while some of the barriers to vaccine uptake included vaccine safety and efficacy concerns and inadequate awareness of vaccination sites and vaccine types. Enablers of handwashing practices encompassed hand hygiene programs and access to soap and water while those of COVID-19 vaccine uptake included improved access to vaccine knowledge and, socio-economic factors like a higher level of education. This review underscores the pivotal role of addressing these barriers while capitalizing on enablers to promote vaccination and handwashing practices. Stakeholders should employ awareness campaigns and community engagement, ensure vaccine and hygiene resources’ accessibility, and leverage socio-economic incentives for effective COVID-19 prevention and control. Clinical trial registration: [https://clinicaltrials.gov/], identifier [CRD42023396303].